THE IMPACT OF ANIMATED VIDEOS ON STUDENTS' VOCABULARY ACQUISITION OF EFL STUDENTS - Lukmanul Hakim; Reyza Amelia Caesari; Syamsul Bahri (Universitas Islam Negeri Ar-Raniry, 2026)
This study aims to examine the effect of animated videos on the vocabulary acquisition of eighth-grade EFL students at MTsN 2 Aceh Besar in the 2025/2026 academic year. The research employed a quantitative pre-experimental design using a one-group pre-test and post-test approach. The sample consisted of 32 students. Data were collected using a 100-item multiple-choice vocabulary test that had been tested for validity and reliability, with a reliability coefficient of 0.986.The results showed that animated videos had a positive impact on students’ vocabulary acquisition. The mean score increased from 53.97 in the pre-test to 78.34 in the post-test, with a gain of 24.37 points. Before the treatment, most students were in the failing category, while after the treatment, no students remained in that category. Some students even reached the good and excellent levels. Therefore, animated videos are proven to be an effective learning medium for improving vocabulary acquisition through engaging and easily understood audio-visual content.